2011
DOI: 10.1016/j.sjbs.2010.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of nerve growth factor in the amniotic fluid during chick embryonic development

Abstract: Nerve growth factor (NGF) and most neurotrophic factors support the proliferation and survival of particular types of neurons. Besidesthe pivotal role of NGF in the development of neuronal cells, it also has important functions on non-neuronal cells. The amnion surrounds the embryo, providing an aqueous environment for the embryo. A wide range of proteins has been identified in human amniotic fluid (AF). In this study, total protein concentration (TPC) and NGF level in AF samples from chick embryos were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Therefore, bringing fluid into the mouth to be swallowed is likely the fundamental process common to all developing vertebrates. For example, it is known that fetal swallowing of amniotic fluid emerges right after major organogenesis around 10–14 weeks of gestation in human and is observed in early development of chicks, sheep, rodents, and monkeys ( Ross and Nijland, 1998 ; Delaney and Arvedson, 2008 ; Mashayekhi et al, 2011 ; Gross and Trapani-Hanasewych, 2017 ; Maynard et al, 2020 ). This process of transporting fluid into the body is repeatedly executed and requires coordinated activation of oropharyngeal muscles ( Sherman et al, 1990 ).…”
Section: A Hypothesis: How Conserved Embryonic Hindbrain Generates Circuits For Diverse Modes Of Feeding and Breathingmentioning
confidence: 99%
“…Therefore, bringing fluid into the mouth to be swallowed is likely the fundamental process common to all developing vertebrates. For example, it is known that fetal swallowing of amniotic fluid emerges right after major organogenesis around 10–14 weeks of gestation in human and is observed in early development of chicks, sheep, rodents, and monkeys ( Ross and Nijland, 1998 ; Delaney and Arvedson, 2008 ; Mashayekhi et al, 2011 ; Gross and Trapani-Hanasewych, 2017 ; Maynard et al, 2020 ). This process of transporting fluid into the body is repeatedly executed and requires coordinated activation of oropharyngeal muscles ( Sherman et al, 1990 ).…”
Section: A Hypothesis: How Conserved Embryonic Hindbrain Generates Circuits For Diverse Modes Of Feeding and Breathingmentioning
confidence: 99%
“…Additionally, ceAF can be a source or supplement of cell culture medium (Larsen 1993 ; Wang et al 1997 ). Previous reports have shown that ceAF contains a variety of growth-related factors like nerve growth factor (NGF), transforming growth factor-β (TGF-β), vascular endothelial growth factor (VEGF), insulin-like growth factor (IGF)-I, and IGF-II (tenBusch et al 1997 ; Karcher et al 2005a , 2005b ; Mashayekhi et al 2011 ; Pressman et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%